ANTI ATHEROSCLEROTIC EFFECT OF ADIPONECTIN - Hidayati, Hanik Badriyah (Malang Neurology Journal, 2015)
Atherosclerosis is a chronic, inflammatory disease of the arterial wall. Atherosclerosis underlies many of the common causes of cardiovascular morbidity and mortality, including myocardial infarction (MI), peripheral vascular disease, and cerebrovascular. Cardiovascular disease (CVD) has become the most frequent cause of death globally and then stroke is the second leading cause of death worldwide and a major cause of long-term disability.Recent study shows that adiponectin exhibits potent antiatherosclerotic effects. Adiponectin is a protein secreted specifically from adipose tissue. Adiponectin has a potential inhibitory effect on all molecular mechanisms of atherosclerosis.